2009
DOI: 10.1080/00016340902883133
|View full text |Cite
|
Sign up to set email alerts
|

Skin adhesive versus subcuticular suture for perineal skin repair after episiotomy – a randomized controlled trial

Abstract: Perineal skin closure using adhesive glue is faster than subcuticular suture, and associated with a similar incidence of complications and pain in the first 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Forty‐eight randomised controlled trials, reporting data from 20 308 women, were included (Table S1). Seventeen interventions were evaluated, including different techniques (17 trials; 35%), different suture materials (six trials; 13%), and biofeedback (three studies; 6%). The majority of trials (71%) were published in general obstetrics and gynaecology journals.…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐eight randomised controlled trials, reporting data from 20 308 women, were included (Table S1). Seventeen interventions were evaluated, including different techniques (17 trials; 35%), different suture materials (six trials; 13%), and biofeedback (three studies; 6%). The majority of trials (71%) were published in general obstetrics and gynaecology journals.…”
Section: Resultsmentioning
confidence: 99%
“…Surgical adhesives have been employed for decades in other specialties, but their use in obstetrics and gynecology is relatively limited. The few published studies employing the use of surgical glue as an adjunct to perineal wound closure have shown varied results in terms of postpartum pain. In all of these studies, the vaginal incision and deep perineal tissues were sutured, and the perineal skin was closed using a surgical adhesive.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized controlled trial comparing the use of surgical adhesive to suture repair of first‐degree perineal lacerations, Feigenberg et al reported less pain, shorter procedure time, and greater patient satisfaction with surgical glue . A randomized trial by Mota et al found no difference in pain between perineal skin closure with suture versus surgical adhesive following mediolateral episiotomy . However, deep pain related to mediolateral episiotomy could have masked skin‐related pain in this study, which may explain why no difference in pain scores was identified between the 2 perineal skin closure methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to our knowledge the current study is the first to compare skin adhesive tape with the interrupted absorbable suture technique in episiotomy skin closure, yet other studies compared adhesive glue to sutures as [14] and [4], targeting a heterogeneous sample of primiparous and multiparous with a total number of 100 and 97 women respectively both supported the potential benefits of glue use, as a better alternative to sutures as regards procedure time and reduced pain sensation although there was insignificant difference between both groups at 7 and 30 days [14]. However, the cost of glue use may be an issue especially in a developing country with limited resources like Egypt, while [15] and [8] reported increase in pain sensation in the sutured arm when comparing skin adhesive tape to suturing the skin in surgeries other than obstetric.…”
Section: Discussionmentioning
confidence: 99%